Can non-fiscal incentives like reverse job work revive the SEZs? The case study of gems and jewellery sector in India - Arpita Mukherjee; Nida Rahman; Eshana Mukherjee (Indian Council for Research on International Economic Relations (ICRIER), 2023)
Globally, special economic zones (SEZs) are created to boost exports and promote investment by providing units located inside the zones with certain fiscal and non-fiscal incentives that are not available to and/or are different from those given to units in the domestic tariff area (DTA). In India, the SEZ Act (2005) and the SEZ Rules (2006) aimed to create a regulatory framework to meet certain objectives, which include attracting private investment, creating employment, and promoting exports. Among the fiscal incentives given to units in Indian SEZs, the income tax benefits are conditional upon the units being net foreign exchange earners (NFE) in five years, which is an export-linked prohibited subsidy under the World Trade Organization's (WTO) Agreement on Subsidies and Countervailing Measures (ASCM). In March 2018, the United States of America (USA) challenged this export-linked subsidy in the WTO and India lost the case in October 2019, requiring the country to withdraw such subsidies. Globally, many countries have designed WTO compliant fiscal incentives and are offering non-fiscal incentives like reverse job work in their SEZs. This has prompted India to design WTO compatible zones and the country is in the process of initiating the Development (Enterprise and Services) Hubs (DESH) Bill, 2022. This Bill has removed the NFE requirement for giving incentives and proposed certain non-fiscal incentives such as reverse job work. This paper explores the costs and benefits of allowing non-fiscal incentives like the reverse job work in Indian SEZs in the gems and jewellery sector, and its likely impact on units both in SEZs and in the DTA. The paper found that India is among the world's top gems and jewellery exporters and this is a key export item from Indian SEZs. Based on secondary data analysis, stakeholder consultations, and a pilot survey, it presents the issues faced by gems and jewellery units in SEZs and makes policy recommendations on how to enhance exports of gems and jewellery from Indian SEZs. As the DESH Bill (2022) evolves, this paper aims to enhance the debate and discussion on incentives in SEZs, based on the requirements of the units and global best practices.
Keywords: L5; F13; L61; 330; World Trade Organisation (WTO); special economic zones (SEZs); international trade; gems and jewellery; subsidies; reverse job work